(untitled) (Conferencea, 2023)
Even in the period of the ancient Turkic language, the verb was considered the most complex, semantically diverse grammatical category compared to all other word groups. In this article, the verbs of the continuous state in “Devoni lugotit turk” were studied in comparison with the verbs listed in “Alisher Navoiy asarlari tilining izohli lugati” and “O‘zbek tilining izohli lugati”. As a result of the development of the period, it was observed that certain changes in the lexeme scheme, that is, the expansion or narrowing of the meaning of some words.